FUN14 Domain Containing 1 (FUNDC1): A Promising Mitophagy Receptor Regulating Mitochondrial Homeostasis in Cardiovascular Diseases - Mao, Yu; Ren, Jun; Yang, Lifang (Frontiers in Pharmacology, 2022)
Mitochondria, the intracellular organelles for cellular aerobic respiration and energy production, play an important role in the regulation of cell metabolism and cell fate. Mitophagy, a selective form of autophagy, maintains dynamic homeostasis of cells through targeting long-lived or defective mitochondria for timely clearance and recycling. Dysfunction in mitophagy is involved in the molecular mechanism responsible for the onset and development of human diseases. FUN14 domain containing 1 (FUNDC1) is a mitochondrial receptor located in the outer mitochondria membrane (OMM) to govern mitophagy process. Emerging evidence has demonstrated that levels and phosphorylation states of FUNDC1 are closely related to the occurrence, progression and prognosis of cardiovascular diseases, indicating a novel role for this mitophagy receptor in the regulation of mitochondrial homeostasis in cardiovascular system. Here we review mitophagy mediated by FUNDC1 in mitochondria and its role in various forms of cardiovascular diseases.